2021
DOI: 10.4082/kjfm.20.0184
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Use of Dietary Supplement and Psychological Status of Cancer Survivors in Korea: A Cross-Sectional Study

Abstract: Background: Dietary supplements (DS) use is known to be common among cancer survivors. However, detailed information on the factors influencing DS use seems insufficient, including cancer-related and psychological factors.Methods: Study subjects were 1,852 Korean adult cancer survivors recruited from cancer survivor clinic of two university-affiliated hospitals. Data were collected retrospectively through review of medical records and self-administered questionnaires. Psychological factors were assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
4
2
Order By: Relevance
“…In addition, the multiple linear regression model showed that anxiety was not associated with higher use of supplements. Although this nding was incompatible with the ndings of another study in Korea [13], there could be several reasons to explain it, including the low sample size, potential confounding, or an intermediate effect related to other factors included in the model. In addition, excessive daytime sleepiness was associated with supplement use in the bivariate analysis, but not the multivariate regression; similar explanations could be given.…”
Section: Prevalence Of Supplement Use and Its Association With Anxiet...contrasting
confidence: 84%
See 2 more Smart Citations
“…In addition, the multiple linear regression model showed that anxiety was not associated with higher use of supplements. Although this nding was incompatible with the ndings of another study in Korea [13], there could be several reasons to explain it, including the low sample size, potential confounding, or an intermediate effect related to other factors included in the model. In addition, excessive daytime sleepiness was associated with supplement use in the bivariate analysis, but not the multivariate regression; similar explanations could be given.…”
Section: Prevalence Of Supplement Use and Its Association With Anxiet...contrasting
confidence: 84%
“…Socio-demographic and cancer-related characteristics study suggested that supplement users were predominately female, like many other studies [13,21]. Unlike previous studies, in this study, age, income, cancer type, and cancer treatment modality were not associated with the use of supplements among cancer patients [4,5,13].…”
Section: Prevalence Of Supplement Use and Its Association With Anxiet...contrasting
confidence: 42%
See 1 more Smart Citation
“…At this time, there are many studies that examine the effect of dietary supplements, such as probiotics [ 46 , 47 ], B-complex multivitamin/mineral supplementation [ 48 ], magnesium [ 49 ], and omega-3 [ 50 ] for anxiety, but there are few reports on whether anxiety towards health encourages people to use dietary supplements. Anxiety was associated with dietary supplement/complementary alternative medicine in cancer survivors [ 51 ], women with early breast cancer [ 52 ], and patients with liver disease [ 53 ] but not healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A separate analysis of breast cancer survivors was not performed in this Korean study, probably because of the small number of breast cancer survivors (59 women) included in the study [ 14 ]. In our previous study, being female was related to a higher probability of long-term DS use, and among female cancer survivors, breast cancer survivors were less likely to take DS compared with female survivors of other cancers such as stomach cancer [ 15 ]. This finding pointed to the necessity of further examining the patterns and related factors of DS use by breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%